Frequency of Mullerian Duct Abnormalities - Humaira Rani , Sobia Nawaz , Nadia Saif , Asma Tanveer Usmani (Journal of Rawalpindi Medical College, 2009)
Background: To determine frequency of most common mullerian duct abnormalities. Methods: In this interventional study, twenty seven patients were studied in which mullerian duct anomalies were detected. They were selected by convenience sampling. All relevant information was written on a designed proforma. All patients with primary amenorrhoea, primary infertility, dysparunia, aparunia, severe dysmenorrhoea, recurrent pregnancy loss and preterm labour were included, while patients with secondary amenorrhoea and secondary infertility were excluded. Results: Out of twenty seven, 25 were 13—30 years of age, two patients were 35 and 52 years of age. 51.9% were married, 40.7% unmarried and 7.4% were divorced. Patients having amenorrhoea were 55.6% while 44.4% had regular menstrual cycle. The most common Mullerian duct anomaly detected was blind end vagina with absent uterus (22.2%).Three patients had transverse vaginal septum (11.1%), 3(11.1%) had longitudinal vaginal septum and 3(11.1%) had vaginal agenesis only. Two (7.4%) patients each had double uterus and subseptate uteri respectively. Conclusion: Mullerian duct anomalies are the commonest cause of primary amenorrhoea but frequency of presentation to hospital is very low. It may be due to poor knowledge and shyness of parents as well as patients. We have to educate them that it is treatable and their daughters can become active members of society.